Proximal embolization of Edwards SAPIEN prosthesis in transcatheter aortic valve implantation - İsa Öner Yüksel; Erkan Köklü; Şakir Arslan; Göksel Çağırcı; Selçuk Küçükseymen (KARE Publishing, 2016)
Transcatheter aortic valve implantation (TAVI) is considered an alternative therapy in high-risk patients with severe aortic stenosis (AS). However, this minimally invasive procedure carries potential complications, such as valve embolization at time of TAVI. We present a case of balloon-expandable aortic valve embolization which was managed nonsurgically. Valve embolization was managed conservatively, as the patient refused open heart surgery for definitive treatment. The patient was transferred to the intensive care unit in stable hemodynamic condition and discharged 1 week following the procedure.